Uji Sistem Dispersi Padat Kofein Dengan Menggunakan Polivinil Pirolidon (PVP) K-30 - Maria Dona Octavia; Auzal Halim; Sari Kartika (Jurnal Farmasi Higea, 2013)
The research about solid dispersion test of coffein used Polvinil pyrrolidone (PVP) K-30. In the current study using solid dispersion coffein using Polyvinyl pyrrolidone (PVP) K-30 and a mixture of physics. coffein manufacture solid dispersion using Polyvinyl pyrrolidone (PVP) K-30's, using the method of dissolution. The parameters tested were melting range, lift angle, specific gravity, Hausner factor, compressibility, porosity, water content, particle size distribution, the absorption of water, microscopic analysis and dissolution. Result of research coffein solid dispersion system using Polyvinyl pyrrolidone (PVP) K-30 can increase the solubility Kofein compared with the mixed form of physics. The percent of dissolution of the best in the 35th minute was the solid dispersion formula 4: 6, amounting to 79.34% compared with other formula.